ANALISIS MENU ENGINEERING DALAM UPAYA MENINGKATKAN PROFITABILITAS DI RESTORAN KUBU AT MANDAPA, BALI - Vina; Imam Ardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the instability of sales revenue and the high number of reservation cancellations at Kubu at Mandapa Restaurant, Bali, indicating that not all menu items contribute optimally to the restaurant's profitability. The Ubud area recorded 265 restaurants in 2024, making it the most competitive culinary district in Gianyar Regency, requiring every restaurant to maintain an effective menu management strategy. This study aims to analyze the popularity index, contribution margin, and menu classification based on menu engineering, as well as to formulate profitability improvement strategies at Kubu at Mandapa Restaurant. This study employed a descriptive quantitative approach, with primary and secondary data collected through sales data for the period of January to December 2025, selling prices, and food cost data obtained via documentation, unstructured interviews, and participant observation. The analytical methods used include menu mix percentage analysis, contribution margin analysis, menu engineering worksheet analysis, and menu engineering-based profitability improvement strategy analysis. Based on the analysis of 21 menu items over a one-year period, menus were classified into 4 categories: 19.05% or 4 items as Star, 38.10% or 8 items as Plowhorse, 9.52% or 2 items as Puzzle, and 33.33% or 7 items as Dog. Star category menus are maintained by preserving consistency in taste, ingredient quality, portion size, and presentation standards, as well as by positioning them as flagship items in the restaurant's promotion. Plowhorse category menus are modified through raw material cost efficiency, recipe and portion adjustment, and gradual, selective selling price review. Puzzle category menus are enhanced through suggestive selling, storytelling, and repositioning within the menu list. Dog category menus are critically evaluated through recipe modification, repositioning, integration into set menus, or r